2014
DOI: 10.1002/anie.201308389
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Adaptations of Structural Dynamics in an Intrinsically Disordered Protein Complex

Abstract: Intrinsically disordered proteins (IDPs) play crucial roles in protein interaction networks and in this context frequently constitute important hubs and interfaces. Here we show by a combination of NMR and EPR spectroscopy that the binding of the cytokine osteopontin (OPN) to its natural ligand, heparin, is accompanied by thermodynamically compensating structural adaptations. The core segment of OPN expands upon binding. This "unfolding-upon-binding" is governed primarily through electrostatic interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
68
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 31 publications
9
68
0
8
Order By: Relevance
“…ID regions may remain dynamic and exhibit a fast exchange of conformations in the complex state [FC0072 (22)]. Fuzzy assemblies can also be generated by ‘unfolding upon binding’ [FC0100 (23)]. Fuzzy regions do not appear in crystal structures of the protein complex, as indicated by missing electron density.…”
Section: Definitionsmentioning
confidence: 99%
“…ID regions may remain dynamic and exhibit a fast exchange of conformations in the complex state [FC0072 (22)]. Fuzzy assemblies can also be generated by ‘unfolding upon binding’ [FC0100 (23)]. Fuzzy regions do not appear in crystal structures of the protein complex, as indicated by missing electron density.…”
Section: Definitionsmentioning
confidence: 99%
“…Paramagnetic relaxation enhancements for spin-labeled cysteine mutants of OPN showed that the heparin-binding site becomes more rigid upon heparin interaction, compensated for elsewhere in the molecule by an increase in the flexibility. The heparin binding site of OPN is a positively charged patch near residue 155, but substantial other stretches of the OPN peptide chain are negatively charged and displaced on heparin binding [24].…”
mentioning
confidence: 99%
“…Most importantly,t he glycine residues are not observable in the absence of heparin. [20] This exposure accelerates exchange with hyperpolarized HDO,t hereby rendering them amenable to detection. This leads to distinct effects in the glycine region.…”
mentioning
confidence: 99%